Matrix metalloproteases and TIMPs as prognostic biomarkers in breast cancer patients treated with radiotherapy: A pilot study. Issue 1 (30th September 2019) - Olivares‐Urbano, María Auxiliadora; Griñán‐Lisón, Carmen; Zurita, Mercedes; del Moral, Rosario; Ríos‐Arrabal, Sandra; Artacho‐Cordón, Francisco; Arrebola, Juan Pedro; González, Amanda Rocío; León, Josefa; Antonio Marchal, Juan; Núñez, María Isabel
Abstract: Breast cancer (BC) is the most common tumour in women and one of the most important causes of cancer death worldwide. Radiation therapy (RT) is widely used for BC treatment. Some proteins have been identified as prognostic factors for BC (Ki67, p53, E‐cadherin, HER2). In the last years, it has been shown that variations in the expression of MMPs and TIMPs may contribute to the development of BC. The aim of this pilot work was to study the effects of RT on different MMPs (‐1, ‐2, ‐3, ‐7, ‐8, ‐9, ‐10, ‐12 and ‐13) and TIMPs (‐1 to ‐4), as well as their relationship with other variables related to patient characteristics and tumour biology. A group of 20 BC patients treated with RT were recruited. MMP and TIMP serum levels were analysed by immunoassay before, during and after RT. Our pilot study showed a slight increase in the levels of most MMP and TIMP with RT. However, RT produced a significantly decrease in TIMP‐1 and TIMP‐3 levels. Significant correlations were found between MMP‐3 and TIMP‐4 levels, and some of the variables studied related to patient characteristics and tumour biology. Moreover, MMP‐9 and TIMP‐3 levels could be predictive of RT toxicity. For this reason, MMP‐3, MMP‐9, TIMP‐3 and TIMP‐4 could be used as potential prognostic and predictive biomarkers for BC patients treated with RT.